2022
DOI: 10.3389/fpls.2022.793904
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis and Responses to Selection in Orange-Fleshed Sweetpotato (Ipomoea batatas L.) Improved Using Reciprocal Recurrent Selection

Abstract: Sweetpotato is a highly heterozygous hybrid, and populations of orange-fleshed sweetpotato (OFSP) have a considerable importance for food security and health. The objectives were to estimate heterosis increments and response to selection in three OFSP hybrid populations (H1) developed in Peru for different product profiles after one reciprocal recurrent selection cycle, namely, H1 for wide adaptation and earliness (O-WAE), H1 for no sweetness after cooking (O-NSSP), and H1 for high iron (O-HIFE). The H1 popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 36 publications
0
21
1
Order By: Relevance
“…were subsequently observed (Diaz et al, 2021;Grüneberg et al, 2022). The strikingly low mid-parent mid-offspring association in the EA breeding platform observed in this study might underline the importance of determining the breeding value of parents on the basis of offspring performance and the selection of parents using their combining ability.…”
Section: Crop Sciencementioning
confidence: 56%
See 1 more Smart Citation
“…were subsequently observed (Diaz et al, 2021;Grüneberg et al, 2022). The strikingly low mid-parent mid-offspring association in the EA breeding platform observed in this study might underline the importance of determining the breeding value of parents on the basis of offspring performance and the selection of parents using their combining ability.…”
Section: Crop Sciencementioning
confidence: 56%
“…The HEBS concept in sweetpotato has been previously described (David et al, 2018;Diaz et al, 2021;Grüneberg et al, 2015): heterosis increments can be determined by comparing (a) the parental mean with the mean across the segregating offspring clones (Diaz et al, 2021;Grüneberg et al, 2022), and/or (b) comparing the mean estimates of intraand inter-gene pool crosses. The latter approach was used in the fundamental maize study by Moll et al (1965), where homozygous inbreed lines were still too weak to be used in hybrid breeding.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, population derived from Tio-joe and ACAB220, and population derived from Vobodouaho and ACAB220. Positive heterosis effects were reported for resistance to sweetpotato virus diseases, storage root yield, beta-carotene and dry matter content (Ngailo et al 2019), and explored using poly-cross and diallel mating design (Musembi et al 2015;Naidoo et al 2016;Baafi et al 2017;Mbusa et al 2018), bi-parental crossing (Afuape et al 2019) and reciprocal recurrent selection (Grüneberg et al 2022). So far, VOBO genotypes can be used for further backcrossing to stabilise beta-carotene content in the background of Vobodouaho.…”
Section: Resultsmentioning
confidence: 99%
“…Afuape et al (2019) reported the possibility to combined elevated content of antagonist quality traits such as dry matter and betacarotene using biparental crossing. Grüneberg et al (2022) reported large genetic gains for tuber yield https://doi.org/10.17221/104/2022-CJGPB and other quality traits (iron and zinc micronutrients) in OFSP hybrids developed from reciprocal recurrent selection. The current research aimed at developing OFSP genotypes that meet the food culture of local communities in Benin and other West African countries.…”
mentioning
confidence: 99%
“…Population improvement aims at the selection of a "best" set of parents to generate new genetic variation around an improved population mean over recurrent cycles of parental selections, whereas variety extraction aims at the selection of the best or very few best clones with complete or nearly complete exploitation of the genetic variation in breeding populations. For an overview of a comprehensive breeding scheme for sweetpotato, comprising population improvement and variety development, see Grüneberg et al (2022). This study provides a valid data set for estimating VarComp and correlations among traits needed to compare selection scenarios in later breeding stages after the selection in first yield trials targeting population improvement and considers multistage selection for "OFSP dry and starchy" within the humid tropics of the Amazon basin.…”
Section: Core Ideasmentioning
confidence: 99%